Community-Based Education Model Effect on Hypertension Patient Compliance in Majaran: a Social Ecological Approach - Manurung, Romianti; Motuho Mendrofa , Fery Agusman (Jurnal Locus Penelitian dan Pengabdian, 2025)
Hypertension management requires consistent medication adherence, yet compliance rates remain problematic in rural Indonesia. Social-ecological approaches that integrate multiple levels of influence may effectively address this challenge, but evidence from Eastern Indonesia remains limited. This study aimed to determine the effect of a community-based education model with a social-ecological approach on medication adherence among hypertensive patients in Puskesmas Majaran (Majaran Health Center), West Papua. A quasi-experimental study with a pre-post design was conducted, involving 60 hypertensive patients randomly assigned to intervention (n = 30) and control (n = 30) groups. The intervention group received a structured, four-stage community-based education program incorporating social-ecological principles over eight weeks, while the control group received standard care. Data were collected using the Modified Morisky Adherence Scale (MMAS-8) and analyzed using Chi-square, Wilcoxon, Mann–Whitney, and logistic regression tests. After the intervention, the experimental group showed significantly improved medication adherence (p < 0.001), with 76.7% of participants showing improvement (versus 26.7% in the control group). High adherence was achieved by 36.7% of intervention participants, while no control group participants reached high adherence. Family support was significantly associated with adherence in the intervention group (p = 0.003). The Mann–Whitney test confirmed significant differences between groups post-intervention (Z = –3.690, p < 0.001). The duration of hypertension diagnosis was not significantly associated with adherence (p = 0.954). Overall, the community-based education model with a social-ecological approach significantly improves medication adherence among hypertensive patients. This model effectively addresses multiple factors influencing adherence, particularly by strengthening family support systems. Healthcare providers should implement multi-level interventions that engage families and communities rather than focusing solely on individual patients.